Design an Internet of Things-Based LPG Gas Leak Detection System - Mustofa Mustofa; Abdul Fadlil (Universitas Ahmad Dahlan, 2022)
LPG currently plays a big role in human life, both in industry and households. However, since the existence of LPG, there have been many cases of fires caused by LPG gas leaks. Undetected LPG gas leaks can cause sparks and can trigger fires. Therefore, currently an LPG gas detection device is needed. The system designed in this study uses an MQ-6 sensor to detect LPG gas, and NodeMCU as a microcontroller. This system not only detects leaking gas, but can also provide alerts and information to the Blynk application on smartphones by utilizing the Internet of Things (IoT). System testing resulted in an error value in detecting gas of 9.52% and the distance between the system and the smartphone was 500 meters. The sensor can detect gas well when the distance between the gas and the sensor is no more than 10 cm. The system can provide information to the smartphone if a gas leak is detected and can provide alerts by turning on the buzzer and LEDs.